Моделирование подземного нагрева сланцев в электромагнитном поле; Известия вузов. Физика; Т. 54, № 11(3) - Князева А. Г. Анна Георгиевна; Лопатин В. В. Владимир Васильевич; Мартемьянов С. М. Сергей Михайлович; Маслов А. Л. Алексей Леонидович; Хан Вэй (2011, 2011)
Заглавие с экрана